STILLNESS AS A MEANS TO ATTAIN TO THE GODLY PASSION OF LOVE - ZACHAROU, Zacharias (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2023)
This paper explores the role of mental prayer in achieving the image and likeness of God and renouncing worldly passions, bringing hesychastic theory into conversation with the life and outward conditions of modern man.